2018
DOI: 10.5123/s1679-49742018000100016
|View full text |Cite
|
Sign up to set email alerts
|

Preenchimento da Caderneta de Saúde da Criança nos serviços de saúde em Belo Horizonte, Minas Gerais, Brasil*

Abstract: a low proportion of filling was observed, especially in PHC and other services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
25

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 15 publications
0
25
0
25
Order By: Relevance
“…A similar finding was found concerning the Caderneta de Saúde da Criança (Child's Health booklet). 21 The comparison of the results of this study was impaired by the fact that other studies addressing the topic had mentioned only the variables that had higher or lower completion rates were in Juiz de Fora (MG), 7 Recife (PE), 8 Vitória (ES) 10 and Ponta Grossa (PR). 22 In all of them, the referred rates were similar to those observed in Rio Grande, suggesting that the lack of standardized completion also occurred in other locations.…”
Section: Discussionmentioning
confidence: 81%
“…A similar finding was found concerning the Caderneta de Saúde da Criança (Child's Health booklet). 21 The comparison of the results of this study was impaired by the fact that other studies addressing the topic had mentioned only the variables that had higher or lower completion rates were in Juiz de Fora (MG), 7 Recife (PE), 8 Vitória (ES) 10 and Ponta Grossa (PR). 22 In all of them, the referred rates were similar to those observed in Rio Grande, suggesting that the lack of standardized completion also occurred in other locations.…”
Section: Discussionmentioning
confidence: 81%
“…In the S2. 21 study, it was observed a low frequency of completion of essential items for developmental follow-up, and despite the filling of the weight and head circumference charts in the first year of life, 62.7% and 51.8% of CHBs, respectively, notes on neuropsychomotor development corresponded to only 6.0% of the books. It was also observed the non-filling of odontogram (99.2%) and dental eruption field (98.6%) of CHB.…”
Section: Limamentioning
confidence: 85%
“…Subtracted from these, 222 did not respond to the research question. We included, as final sample, 15 articles, [8][9][10][11][12][13][14][15][16][17][18][19][20][21] that are integrated into the corpus of the study for analysis and discussion. These articles were evaluated as to the level of evidence in: Level I -results from the meta-analysis of multiple controlled and randomized clinical studies; Level IIevidences resulting from individual studies with experimental design; Level III -findings from quasi-experimental studies; Level IVevidences of descriptive studies or qualitative approach; Level V -case or experience reports and Level VI -evidence based on expert opinions.…”
Section: Methods Introductionmentioning
confidence: 99%
“…[3][4]7 In addition, although one of the nurses emphasized in his speech the importance of encouraging and supporting breastfeeding, it is still necessary to pay attention to this issue in order to promote proper and healthy eating. It is revealed, according to a study 21 carried out in Minas Gerais on the completion of the Child Health Handbook, that the type of food at discharge from maternity was one of the least filled, which undermines child health surveillance and communication between health professionals.…”
Section: Discussionmentioning
confidence: 99%